Comparative literature : a critical introduction - Bassnett, Susan (Oxford, UK : Cambridge, USA : Blackwell, 1993)
This major new introduction to comparative literature is for the students coming to the subject for the first time. Through an examination of a series of case studies and new theoretical developments, Bassnett reviews the current state of comparative literature world--wide in the 1990s.
Includes bibliographical references (p. [175]-180) and index.
Keywords: Comparative literature; Literature, Modern; Criticism